Analisis Semiotika John Fiske terhadap Representasi Kedekatan Emosional Orang Tua dan Anak dalam Film “Pulang” - Rizky, Rio; Kusnarto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Emotional closeness is fundamental in a harmonious family which is often implemented with interaction between parents and children, but interaction is not always the main thing but behavior, habits, touch or physical contact also greatly affect emotional closeness. This study aims to explore the form of emotional closeness that is formed between parents and children in the film ‘Pulang’, the theme of the film is family conflict which focuses on Pras (Ringgo Agus) and Rindu (Ziva Magnolya) during their trip to Jogjakarta. By using John Fiske's semiotic analysis with its three levels, the research results can be presented in the form of a representation of emotional closeness at the level of reality which is confirmed through dynamic interactions, freedom of expression and gestures as a form of care and affection. The level representation highlighted in the camera technique (shots) has shown signs at the level of reality as evidenced by the interactions between the characters. The ideological level found is Liberalism which is applied in parenting, education and early child development by parents in influencing emotional closeness. Then the form of emotional closeness that is formed is a secure attachment pattern that constructs a high emotional reality closeness to the characters Pras and Rindu.